Effect of pro-degradant additive on photo-oxidative aging of polypropylene film - Noor Zalikha Mohamed Islam,; Nadras Othman,; Zulkifli Ahmad,; Hanafi Ismail, (Universiti Kebangsaan Malaysia, 2011)
This paper describes the effect of pro-degradant additives (PDA) on photo-oxidative aging of polypropylene (PP) films after being time accelerated in UV-weathering chamber. Thin films (0.12 mm) containing these additives were prepared by sheeting process. The effect of UV on PP films in the presence of these additives was investigated. Changes in the PP films appearance, tensile properties and carbonyl index (CI) were used to investigate the degradation behavior. The films became completely pulverised after 100 h of photo-oxidative treatment and could not be tested further. Films containing PDA showed rapid loss in tensile properties within 100 h of photo-oxidative aging. In addition, the CI results of photo-oxidative films increased with increasing PDA amount within the time interval of aging and the activity was due to the mechanism reaction of PP with PDA particles. During the aging process the material becomes denser due to tighter packing and incorporation of oxygen into the amorphous regions of the polymer. The results indicated that the presence of PDA contributed to the photo degradation and the activity was very much influenced by the amount PDA